2016
DOI: 10.1371/journal.pone.0151960
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in PCOS Patients Enhances Oxidative Stress and Leukocyte Adhesion: Role of Myeloperoxidase

Abstract: Cardiovascular diseases and oxidative stress are related to polycystic ovary syndrome (PCOS) and insulin resistance (IR). We have evaluated the relationship between myeloperoxidase (MPO) and leukocyte activation in PCOS patients according to homeostatic model assessment of IR (HOMA-IR), and have explored a possible correlation between these factors and endocrine and inflammatory parameters. This was a prospective controlled study conducted in an academic medical center. The study population consisted of 101 PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 45 publications
2
66
2
1
Order By: Relevance
“…The white blood cell counts in the peripheral blood of patients with PCOS and hyperinsulinemia increased along with hyperandrogen production [91] and mainly increased in macrophages and neutrophils, which infiltrate this excessive fat to "clean up" dysfunctional and dead cells, resulting in a state of chronic low-grade inflammation [11]. As PCOS is usually treated with oral contraceptive and metformin [92], the number of macrophages and neutrophils may become even higher under treatment with oral contraceptive monotherapy and could be improved with metformin [91]. Besides its better-known effects in the improvement of oxidative stress and insulin resistance, metformin is also an effective treatment for immune-related disorders.…”
Section: Other Immunological Mechanisms Of Pcosmentioning
confidence: 99%
“…The white blood cell counts in the peripheral blood of patients with PCOS and hyperinsulinemia increased along with hyperandrogen production [91] and mainly increased in macrophages and neutrophils, which infiltrate this excessive fat to "clean up" dysfunctional and dead cells, resulting in a state of chronic low-grade inflammation [11]. As PCOS is usually treated with oral contraceptive and metformin [92], the number of macrophages and neutrophils may become even higher under treatment with oral contraceptive monotherapy and could be improved with metformin [91]. Besides its better-known effects in the improvement of oxidative stress and insulin resistance, metformin is also an effective treatment for immune-related disorders.…”
Section: Other Immunological Mechanisms Of Pcosmentioning
confidence: 99%
“…20 Percentage of A1c was measured with an automatic glycohemoglobin analyzer (Arkray Inc., Kyoto, Japan), and high-sensitive C-reactive protein (hsCRP) levels were quantified by an immunonephelometric assay. Levels of glucose, total cholesterol (TC) and triglycerides (TG) in serum were determined by means of an enzymatic method.…”
Section: Biochemical Determinationsmentioning
confidence: 99%
“…Obese patients were classified as IR obese when the HOMA index was >2.5 and non-IR obese when the HOMA index was <2.5, as in a previously published study. 20 Percentage of A1c was measured with an automatic glycohemoglobin analyzer (Arkray Inc., Kyoto, Japan), and high-sensitive C-reactive protein (hsCRP) levels were quantified by an immunonephelometric assay.…”
Section: Biochemical Determinationsmentioning
confidence: 99%
“…For instance, Victor et al [27] showed that IR in PCOS patients enhanced oxidative stress and leukocyte adhesion. Kocer et al [28] demonstrated that metformin improved PCOS, probably by decreasing oxidative stress and improving IR.…”
Section: Resultsmentioning
confidence: 99%